2022
DOI: 10.7150/ijbs.67529
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Licensing Factors: Novel Targets for Cancer Therapy via Inhibiting the Stemness of Cancer Cells

Abstract: The replication licensing factors strictly regulate the DNA replication origin licensing process to guarantee the stability of the genome. Numerous experimental studies have recently demonstrated that the replication licensing factors as oncogenes are essential for the occurrence and development of cancers. Drug resistance, being one of the main characteristics of cancer stem cells, can cause a high recurrence rate and a low survival rate in patients with different cancers. However, the function of the replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…It was identified that HCT116 colon cancer cells initiate DNA replication normally in the absence of ORC5 and ORC2 proteins [ 88 ]. Additionally, ORC2 was associated with prevention of apoptosis induction and could serve as a potential target for cancer therapy by inhibition of cancer cell stemness [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that HCT116 colon cancer cells initiate DNA replication normally in the absence of ORC5 and ORC2 proteins [ 88 ]. Additionally, ORC2 was associated with prevention of apoptosis induction and could serve as a potential target for cancer therapy by inhibition of cancer cell stemness [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“… 219 , 220 (b) Aberrant DNA replication license system induces abnormal DNA replication, increasing genomic instability, and carcinogenesis. 221 , 222 In addition, spontaneous mutation of MCMs increases chromosome elimination and DNA damage, 223 whereas a more than twofold reduction of MCM protein expression could lead to genomic instability in S. cerevisiae . These findings demonstrated that MCMs are indeed involved in tumorigenesis, but the detailed mechanism is still unclear.…”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
“…However, dysregulation of the cell cycle‐dependent kinase CDK permits MCMs constantly binding to each other, resulting in continuous cell division and high expression 219,220 . (b) Aberrant DNA replication license system induces abnormal DNA replication, increasing genomic instability, and carcinogenesis 221,222 . In addition, spontaneous mutation of MCMs increases chromosome elimination and DNA damage, 223 whereas a more than twofold reduction of MCM protein expression could lead to genomic instability in S. cerevisiae .…”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
“…Three complexes with ubiquitin ligase activity are responsible for inhibiting CDT1 activity, namely SKP1cullin-1-F-box protein containing SKP2 complex (SCF SKP2 ), denticleless E3 ubiquitin protein ligase homolog CUL4-DDB1 CDT2 and the anaphase-promoting complex/cyclosome-CDH1 (APC/C) CDH1 complex (13,17). Several studies have shown that deregulation of DNA replication-licensing factors is significantly implicated in cancer (18)(19)(20). Overexpression of CDT1 has been reported to promote carcinogenesis through increased genomic instability (14,21,22).…”
mentioning
confidence: 99%